Justification of criteria for assessing the inertia of tribosystems - Войтов, В. А.; Бекиров, А. Ш.; Войтов, А. В. (Problems of Tribology, 2019)
A definition of the inertia of the tribosystem is proposed, as the length of time after which the tribosystem is able to respond to changes in input (load changes, sliding speed, lubricating medium), realizing the transformation of the mechanical energy of deformation of roughness and material of the surface layers into heat, dissipating it into the environment, thereby adapting (adapting) to input effects, dimension - second. This property allows the tribosystem to return to its original steady state after exposure to external disturbances. The criteria for estimating the inertia of tribosystems to a change in external influences are theoretically substantiated and experimentally confirmed. It is established that small values of the criterion Т1 associated with the rapid equalization of temperatures throughout the triboelement in the run-in process, and small values of the criteria Т2,I and Т2,f – rapid restructuring of the surface layers and roughness of friction surfaces. The relationship between the values of the inertia criteria and the time of running-in has been established. It is shown that in order to reduce the time of running-in it is necessary to decrease the values Т1 and Т2,I , Т2,f, for this, it is necessary to reduce the volumes of triboelements, increase the thermal diffusivity of materials and increase the sliding speed at the final stage of burn-in. Key words: tribosystem, modeling; transient processes, breaking-in, inertness of the tribosystem, running-tribosystem, run-in time.